İsveç ve Türkiye’deki farklı STK’ların gözünden Suriyeli mülteci krizi - Çınar, Sıla Sezge (İstanbul Bilgi Üniversitesi, 2017)
[Abstract Not Available]
The Syrian refugee crisis from the perspectives of different NGOs in Sweden and Turkey